Design On-The-Fly for Critically Evaluating Evidence: Informal Poster-Making for Health and Nutrition Students. Issue 1 (2nd January 2019) - Opuda, Eugenia; Bresnahan, Megan
ABSTRACT: Annually, the University of New Hampshire (UNH) Dietetics Internship Program enrolls recent graduates with undergraduate degrees in Nutrition and Dietetics for a 10-month program required to practice as a registered dietician. Each summer, a librarian is invited to introduce these students to library resources relevant to topics in dietetics. This article describes how two librarians collaborated to design a student-centered, active-learning session, informed by the program's learning objectives. The authors detail the development of session learning outcomes, the lesson plan, handouts, active-learning strategies, and classroom management techniques that may be repurposed and flexibly tailored to hospital and academic classroom settings.